In vivo toxicity study of a plant Phyllanthus amarus, in rat - Sirajudeen, K.N.S.; Sulaiman, Siti Amrah; Madhavan, M; Ismail, Zabidah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Introduction: Phyllanthus amarus (P. amarus), a plant species of Euphorbiaceae family, is used as a folk medicine for jaundice and other diseases in Malaysia and other countries. The variation in their efficacy with geographical location and varieties has been reported which has been attributed to their constituent composition. But, so far no toxicity studies have been carried out on this plant with clear documentation, especially with those plants growing in Malaysia. Objective: The aim of this preliminary study was to determine the toxic side effects of aqueous extract of leaves of P. amaros (grown in Malaysia) following oral administration in rats by assessing the morphological, biochemical and histological changes. Materials & Methods: Sprague-Dawley rats weighing (180-230 grams) were used as animal models in this study. Aqueous extract of leaves of P. amarus was administered orally to male rats for acute toxicity study (5 gram I Kg body weight) and to the male and female rats for chronic toxicity study (at the doses of 100, 400 and 800 mg/ Kg body weight/day for six weeks). Control of male and female rats was also maintained without plant extract administration. Body weight of the rats was taken initially and periodically once a week, till the end of experimental period. At the end of experimental period (6 weeks), the rats were sacrificed and analyzed for biochemical markers of liver injury - alanine transaminase (AL T), aspartate transaminase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and total protein in the serum collected and the marker enzymes were assayed in the homogenates of the rat liver. Liver sections were taken for histological studies; Light microscopy, proliferative cell nuclear antigen (PCNA) study and apoptotic study by using ApopTag kit. Results: Acute admininstration of P. amarus extract, orally, even at a dose of 5 gram/Kg body weight) did. not produce any signs of toxicity or mortality. In the chronic study, no significant differences (p>0.05) were obserVed ·between the control and P. amarus extract administered rats in the body weight gain during the experimental period as well as in the biochemical markers analyzed (ALT, AST,ALP,LDH and total protein) in serum and liver homogenates. The non-toxic nature of P. amarus extract administration was confirmed by histological studies i.e., no observable changes were found between control and P.amarus extract administered rats. Conclusion: Acute oral administration of P.amarus extract is non-toxic to the rat liver, even at a dose of 5 gram /kg body weight. The chronic toxicity study of P. amarus extracts adm_ini~tration showe~ the absence of cum ulat1ve toxicity as reflected by the non-stgntficant change tn the parameters studied as well as from the results of the histological studies